Processes of Creation in Anne Sauvagnargues (Revista Apotheke, 2020)
This paper consists in problematize the processes of creation based on the work of Anne Sauvagnargues. For that, it shows an introduction to the conception elaborated by this artist and philosopher. The object of analysis are three of her paintings: “Station Saint Michel”, “Viva Italia!” and “Arrêt à Marseille”. The initial exposure increase, an approximation with the concept of blockage develops - for the author the blockage is who creates - and with the notion of subtraction - since for Sauvagnargues, creation is always subtractive. The hypothesis defended by the trial is that there is a creation theory in Anne Sauvagnargues at the same time is related to the idea of blockage - which could be distinct from a certain understanding about the concept of resistance in Gilles Deleuze: to create is to resist - and with subtraction while invalidating a naturalized law. Naturalization, in turn, prevents the perception that the defense of coherent systems are always impositions of a specific reading. In this direction, the paper´s bet is that Anne Sauvagnargues´ work, seldom translated in Brazil, have important contributions to cartography whose intention is to map relationships that involve the processes of creation and processes of subjectification.
Keywords: processes of cration; Anne Sauvagnargues; Gilles Deleuze; blockage; subtraction